Discharge planning berbasis augmented reality dan teach-back pada keluarga pasien yang menjalani hemodialisis: Analisis hukum dan prinsip etik keperawatan - Sari, Cindy Amalia; Arofiati, Fitri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: The need for hemodialysis services continues to increase due to the high prevalence of kidney disease. The use of Augmented Reality (AR) and the Teach-Back method is necessary to optimize discharge planning and improve understanding among patient families. Purpose: To analyze the legal basis and ethical principles of nursing in implementing Augmented Reality (AR)-based discharge planning and the Teach-Back method for families of patients undergoing hemodialysis. Method: This descriptive study design employed a case study analysis approach. Data collection was conducted using literature review and subsequent data analysis using ethical-conceptual analysis, legal interpretation, and ethical principles of nursing in implementing Augmented Reality (AR)-based discharge planning and the Teach-Back method for families of patients undergoing hemodialysis. Results: Discharge planning implementation in hospitals is still dominated by conventional methods, including oral education and printed media such as pamphlets, which are not optimally utilized. Many patients and families appear to understand, but evaluations of understanding are rarely conducted, so the effectiveness of education in preparing for home care is not guaranteed. Conclusion: Discharge planning implementation that still relies on oral education without evaluation of understanding poses legal risks, violations of nursing ethics principles, and professional accountability. The integration of Augmented Reality (AR) and the Teach-Back method can improve patient and family understanding and ensure information is received accurately and accurately. Keywords: Augmented Reality; Discharge Planning; Nursing Law; Nursing Ethical Principles; Teach-Back Method. Pendahuluan: Kebutuhan layanan hemodialisis terus meningkat seiring tingginya prevalensi penyakit ginjal. Penggunaan Augmented Reality (AR) dan metode Teach-Back diperlukan untuk mengoptimalkan pelaksanaan discharge planning dan meningkatkan pemahaman keluarga pasien. Tujuan: Untuk menganalisis landasan hukum serta prinsip etik keperawatan dalam pelaksanaan discharge planning berbasis Augmented Reality (AR) dan metode Teach-Back kepada keluarga pasien yang menjalani hemodialisis. Metode: Penelitian dengan rancangan deskriptif menggunakan pendekatan analisis studi kasus yang dilakukan pengumpulan data menggunakan studi kepustakaan dan selanjutnya analisis data menggunakan analisis etis-konseptual interpretasi hukum, serta prinsip etik keperawatan dalam pelaksanaan discharge planning berbasis Augmented Reality (AR) dan metode Teach-Back kepada keluarga pasien yang menjalani hemodialisis. Hasil: Pelaksanaan discharge planning di rumah sakit masih didominasi metode konvensional, berupa edukasi lisan dan media cetak seperti pamflet yang tidak dimanfaatkan secara optimal. Banyak pasien atau keluarga tampak mengerti, namun evaluasi pemahaman jarang dilakukan, sehingga efektivitas edukasi dalam mempersiapkan perawatan di rumah belum terjamin. Simpulan: Pelaksanaan discharge planning yang masih mengandalkan edukasi lisan tanpa evaluasi pemahaman menimbulkan risiko hukum, pelanggaran prinsip etik keperawatan, dan akuntabilitas profesional. Integrasi Augmented Reality (AR) dan metode Teach-Back dapat meningkatkan pemahaman pasien dan keluarga, serta memastikan informasi diterima dengan tepat dan benar. Kata Kunci: Augmented Reality; Discharge Planning; Hukum Keperawatan; Metode Teach-Back; Prinsip Etik Keperawatan.